Preparation method of starch-lipid compound
The preparation of starch-lipid complexes by hydrothermal method solves the problems of using many chemical preparations, complex processes and high pollutants in the existing methods, and achieves an efficient and green preparation process, and improves the stability and functionality of the complex.
Patent Information
- Application Number
- CN202411780788.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The existing preparation methods for starch-lipid complexes require the use of more chemical preparations, complex processes, and high pollutants, which are not conducive to industrial production.
The starch-lipid complex is prepared by hydrothermal method. The composite is obtained by preparing amylose or amylopectin and distilled water into a suspension, stirring in an 80°C water bath, dissolved safflower seed oil is added, and the composite is obtained after slow cooling, centrifugation washing and drying.
An efficient and green starch-lipid complex preparation is achieved, the lipid content in the composite product is improved, the swelling, relative crystallinity and thermal stability of the composite are increased, and the production cost is reduced.
Smart Images

Figure CN119586778A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of food processing, and particularly relates to a method for preparing a starch-lipid complex. Background Art
[0002] Starch-lipid complex is an important starch derivative. During the formation of starch-lipid complex, the fatty chains of lipids can be stabilized inside the helical cavity of amylose through hydrogen bonds, hydrophobic interactions, van der Waals forces, etc., and the hydrophilic groups of lipids are exposed to the outside of the helix due to steric hindrance and electrostatic repulsion, which will affect the gelatinization, aging, enzymatic hydrolysis and freeze-thaw stability of starch, and have a beneficial effect on the texture characteristics and nutritional quality of food. Starch-lipid complex utilizes the interaction between natural polymers to achieve copolymerization modification to form a composite system with unique processing characteristics and functional properties, ultimately expanding the application range of natural polymers. On the one hand, it can enhance the functional properties of starch-lipid complexes, thereby expanding the development and utilization of starch in various fields; on the other hand, it can also optimize the processing technology of starch-based foods and guide the production of functional foods and new health products.
[0003] The sustainable development of starch and deep processing industry has received great attention from the industry. As starch-lipid complexes have broad application prospects, artificial synthesis of starch-lipid complexes has become a current research hotspot. However, most of the current synthesis research at home and abroad usually uses pure amylose, debranched starch or gelatinized starch to prepare complexes. These methods require irritating chemical reagents and high reaction temperatures, or are time-consuming and costly, which is not conducive to industrial production. Therefore, it is urgent to develop new processes for the production of efficient and green starch-lipid complexes.
[0004] Therefore, in order to solve the above technical problems, it is necessary to provide a new technical solution to solve this technical problem, especially a method for preparing an efficient and green starch-lipid complex. Summary of the invention
[0005] The purpose of the present invention is to solve the technical problems that the preparation of starch-lipid complexes in existing methods requires the use of more chemical agents, complex processes and high pollutants, and provides a method for preparing starch-lipid complexes.
[0006] In order to achieve the above object, the present invention provides the following technical solution: a method for preparing a starch-lipid complex, characterized in that it comprises the following steps:
[0007] S1. Prepare a suspension of amylose or a mixture of amylopectin and amylose with distilled water to form a starch emulsion with a mass percentage of 30%, and stir it in a water bath at 80°C with a water bath magnetic stirrer for 1 h;
[0008] S2. Take safflower oil and dissolve it in hot anhydrous ethanol, then add the solution to the starch paste in step S1, and then stir in a water bath for 1h;
[0009] S3. The obtained sample was slowly cooled to room temperature, the prepared sample was taken out, centrifuged at 8000 r / min for 15 min, and then centrifuged and washed with a 50% by volume ethanol-water solution, and finally dried in an oven at 45°C overnight, crushed and sieved through a 100-200 mesh sieve.
[0010] Preferably, when the starch is a mixture of amylopectin and amylose, the mixing ratio of amylopectin to amylose is 2:8-3:7.
[0011] Preferably, the safflower seed oil can also be replaced by one of linseed oil, palm oil, soybean oil, corn oil, cottonseed oil, coconut oil, tallow and lard.
[0012] The beneficial effects of the present invention are:
[0013] The present invention prepares starch-lipid complexes by a hydrothermal method, which is a green, low-carbon and efficient technology. Starch undergoes a degradation reaction in a hydrothermal system, causing starch chains to break and the degree of polymerization to decrease. Under hydrothermal conditions, water molecules can more easily penetrate into starch granules, promoting starch expansion in hot water, and amylose can also be more easily dissolved. This characteristic is conducive to promoting the complex reaction of amylose and lipids.
[0014] The moisture content has a certain degree of degradation effect on the starch chain, so it can effectively increase the lipid content in the composite product. In addition, the moisture content can increase the viscosity peak of the viscosity curve of the composite in the cooling stage; with the increase of moisture content, the swelling degree, relative crystallinity and thermal stability of the composite first increase and then decrease. When the moisture content is 30%, the composite product has a relatively high composite efficiency, the largest swelling degree and relative crystallinity, the strongest thermal stability, and the best preparation effect.
[0015] After properly adding amylopectin, the binding effect of amylose and lipids will be increased. Under hydrothermal conditions, amylose and amylopectin will degrade, the degree of polymerization (chain length) of starch will decrease, and the swelling degree and solubility of starch will increase within a certain temperature range. The increase in swelling degree and solubility is conducive to the lipid molecules entering the starch granules or reacting with the amylose molecules outside the granules. When the ratio of amylopectin to amylose is between 3:7 and 2:8, the degradation of amylopectin will reduce the hindrance to the compounding of amylose and lipids, increase the formation of amylose and lipid complexes, and be conducive to the formation of an ordered V-shaped crystal structure and enhance the stability of the amylose-lipid complex.
[0016] Fats and oils are macromolecules that can form complexes through hydrogen bonds and hydrophobic forces. The composite index of the two is higher than that of small molecule fatty acids and starch. The structure of starch is occupied by fats and oils, and amylase cannot occupy the site for digestion, which reduces the digestibility of starch. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The short-range molecular order of Examples 1-5 and Comparative Example 1.
[0018] Figure 2 The X-ray diffraction patterns of Examples 1-5 and Comparative Example 1 are shown.
[0019] Figure 3 The microstructure diagrams of Examples 1-5 and Comparative Example 1.
[0020] Figure 4 The oil absorption change diagram of Examples 1-5 and Comparative Example 1.
[0021] FIG5 is a solubility and swelling force diagram of Examples 1-5 and Comparative Example 1, wherein FIGA is a solubility diagram of the sample; and FIGB is a swelling force diagram of the sample.
[0022] Figure 6 It is the freeze-thaw stability diagram of Examples 1-5 and Comparative Example 1. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0024] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0025] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0026] Example 1
[0027] The preparation method of wheat starch-lipid complex comprises the following steps:
[0028] (1) Weigh 30 g of a mixture of amylopectin and amylose and mix it with distilled water to prepare a starch milk with a mass fraction of 30%, and stir it in a water bath at 80° C. for 1 hour to obtain a swollen starch milk; wherein the mixing ratio of amylopectin to amylose is 2:8-3:7.
[0029] (2) 4.5 g of safflower oil was taken, and the safflower oil was dissolved in hot anhydrous ethanol (above the boiling point of anhydrous ethanol) to prepare a safflower oil-anhydrous ethanol solution with a mass concentration of 10%, and the solution was slowly added to the swollen starch milk obtained in step (1), and the heating and stirring were continued for 1 hour. After the reaction was completed, the solution was cooled to 20° C., centrifuged at a centrifugal force of 8000 r / min for 15 minutes, and repeatedly centrifuged and washed three times with a 50% by volume ethanol solution, dried at 40° C. overnight, crushed and sieved through a 100-mesh sieve to obtain a wheat starch-lipid complex, named WS-SO 30%.
[0030] Example 2
[0031] The preparation steps are the same as those in Example 1, except that the mass fraction is replaced from 30% to 10%, and then compounded with safflower seed oil to obtain a wheat starch-lipid complex, named WS-SO 10%.
[0032] Example 3
[0033] The preparation steps are the same as those in Example 1, except that the mass fraction is replaced from 30% to 20%, and then compounded with safflower seed oil to obtain a wheat starch-lipid complex, named WS-SO 20%.
[0034] Example 4
[0035] The preparation steps are the same as those in Example 1, except that the mass fraction is replaced from 30% to 40%, and then compounded with safflower seed oil to obtain a wheat starch-lipid complex, named WS-SO 40%.
[0036] Example 5
[0037] The preparation steps are the same as those in Example 1, except that the mass fraction is replaced from 30% to 50%, and then compounded with safflower seed oil to obtain a wheat starch-lipid complex, named WS-SO 50%.
[0038] Comparative Example 1
[0039] The preparation steps are the same as those in Example 1, except that the starch is 30 g of straight-chain starch, no hydrothermal treatment is performed (ie, no step of stirring in a water bath at 80° C. for 1 h is performed), and the sample is named WS.
[0040] On the prepared products: after the enzymatic reaction, the structured fat products can maintain the basic level of crude oil, and the acid value and peroxide value are still lower than the national standard level. There is no significant change in nutritional indicators and functional groups, and it has good thermal stability.
[0041] The performance of the product is measured and analyzed, and the measurement method is as follows:
[0042] 1. Determination of short-range molecular order
[0043] A certain amount of starch-lipid complex was mixed with dried potassium bromide at a mass ratio of 1:100, and ground into powder in an agate mortar. After being pressed into tablets using a tablet press, the tablets were placed in a Fourier infrared spectrometer for spectral scanning. Scanning conditions: with air as the background, the scanning band was 4000-400 cm -1 , the number of scans is 64 times, and the scanning resolution is 4cm -1 .
[0044] 2. Crystal structure determination
[0045] Take an appropriate amount of wheat starch and composite samples and place them in the groove of the sample plate, press them with a smooth glass slide, then remove the excess powder to make the sample surface flat. The diffraction conditions are copper target, voltage 44k V, current 27mA, Cu-Kα radiation, measurement angle 2θ = 4-35°, step size 0.05°, scanning speed 5° / min. The relative crystallinity (RC) of the sample is calculated by Jade 6.5 software. The crystallinity calculation formula is as follows:
[0046]
[0047] Ac is the crystalline area; Aa is the amorphous area
[0048] 3. Determination of thermodynamic properties
[0049] A certain amount of sample was weighed and placed in a constant crucible, with an empty dish as a reference. The test conditions were: heating rate of 10°C / min, temperature scanning range of 30-250°C. After the test, Pyris software was used to calculate the changes in To (starting temperature), Tp (peak temperature), Tc (end temperature) and enthalpy value (ΔH).
[0050] 4. Determination of Microstructure
[0051] The powdered sample was gently adhered to the conductive glue, placed in an ion sputtering instrument, and gold-sprayed for 120 seconds. The sample particle morphology was observed in the vacuum sample chamber of a scanning electron microscope, and then SEM observations were performed and photos were taken at different magnifications. The acceleration voltage was 5 kV.
[0052] 5. Oil absorption
[0053] The starch sample was pressed into a cylindrical shape (13 mm in diameter and 2 mm in height) using a tablet press to ensure a smooth surface. The entire round starch sample was placed in a square dish containing safflower seed oil to ensure that the safflower seed oil submerged the starch sample. 10 μL of distilled water was added to the surface of the starch sample using a high-precision injection system and allowed to stand for 2 minutes. When the water droplets no longer changed, photos were taken and recorded. After the test, the circular drop curve was fitted using the La Place-Young equation in the OCA 20 software system to obtain the contact angle value of the sample in safflower seed oil.
[0054] 6. Solubility and swelling power
[0055] Accurately weigh 0.2 g of sample, add 10 mL of pure water to the weighed centrifuge tube m1, keep in a constant temperature water bath at 50, 60, 70, 80, and 90 ° C for 1 h, cool to room temperature, and centrifuge at 3000 r / min for 20 min. After the culture dish m2 is constant weight, fill it with the supernatant, place it in a 105 ° C oven and dry it again to constant weight, recorded as m4, turn the centrifuge tube upside down to drain the water and weigh it, recorded as m3.
[0056]
[0057] 7. Freeze-thaw stability
[0058] Weigh a certain amount of sample, add distilled water to prepare a starch suspension with a mass fraction of 6%, shake well, heat in a 95°C water bath for 30 minutes, cool to room temperature, pour the starch paste into a 5mL centrifuge tube, record the mass of the starch paste W1, put it in a -18°C refrigerator for 24 hours, then take it out and thaw it in a 30°C water bath for 2 hours, centrifuge it at 3500r / min for 20 minutes, pour out the precipitated water after centrifugation, weigh the remaining precipitate mass W2, and repeat the freeze-thaw cycle 5 times according to the above method. The sample water precipitation rate formula is as follows:
[0059]
[0060] W1 is the mass of starch paste (g); W2 is the wet weight of sediment (g).
[0061] Results of determination of short-range molecular order
[0062] like Figure 1As shown, compared with Comparative Example 1 (WS), Examples 1 to 5 thereof exhibit characteristic absorption peaks of triglyceride functional groups: 3016 cm-1 characteristic peak is attributed to the stretching vibration of cis double bonds, 2930 cm-1 is attributed to the stretching vibration of asymmetric CH bonds, 2848 cm-1 is attributed to the stretching vibration of symmetric CH bonds, 1747 cm-1 is attributed to the stretching vibration of C=O, and 1457 cm-1 is attributed to the bending vibration of CH. It can be seen from Examples 1 to 5 that the peak intensities at 2930 cm-1, 2848 cm-1 and 1747 cm-1 first increase and then decrease with the increase of moisture content in wet heat treatment, and the composite effect is better when the moisture content is 30%. The presence of the peak at 1747 cm-1 is related to the formation of starch-lipid complexes in the blend of starch and safflower oil and the presence of free safflower oil in the blend. The smaller absorption is mainly due to the smaller degree of complexation of the product and the smaller content of the formed starch-lipid complex.
[0063] Crystal structure determination results
[0064] like Figure 2 As shown, the crystalline structures of Examples 1 to 5 gradually change from A-type to V-type with the addition of hydrothermal treatment and lipids, with characteristic peaks at 7.6, 13.6, and 20.2, showing the formation of V-type starch-lipid complexes. The relative crystallinity of starch-lipid is mainly determined by the content of free lipids, the double helix structure of amylopectin, and the straight-chain starch-lipid complex with a single helix structure. As the moisture content of the system increases from 10% to 30%, the relative crystallinity of the complex increases from 19.2% to 23.8%. This is because with the increase in the moisture content of the system, straight-chain starch is more likely to migrate, which promotes the formation of straight-chain starch-lipid complexes, making their crystalline structure more compact and stable. When the moisture content of the system continues to increase to 50%, the relative crystallinity of the complex drops sharply to 20.1%. This result corresponds to the gelatinization enthalpy value and the enthalpy value of the starch-lipid complex in the DSC spectrum, indicating that the double helix structure of some amylopectin is unwound and melted to a sharp decrease in its relative crystallinity.
[0065] Thermodynamic properties test results
[0066] As can be seen from Table 1, compared with Comparative Example 1, there are differences in the peak I temperatures of To, Tp and Tc of Examples 1 to 5. As the moisture content of the starch system increases from 10% to 50%, the initial gelatinization temperature of the complex increases from 51.4°C to 64.63°C. The △H of the complex at peak I shows a decreasing trend, because there are more crystalline regions of starch, the double helical structure of amylopectin partially melts and unwinds, and there are fewer amorphous regions. In peak II, the starch-lipid complex undergoes a thermal transition between 140 and 180°C, while there is no corresponding peak in Comparative Example 1. In addition, the enthalpy value of the starch-lipid complex increases with the increase of moisture content (10%-30%). As the moisture content of the system increases, a large amount of amylose overflows, resulting in the formation of an amylose-lipid complex crystalline structure. The Tp and Tc values of the complex at high moisture contents of 40% and 50% decrease slightly due to excessive starch gelatinization during the hydrothermal process. The crystallinity of the complex is the highest when the moisture content is 30%.
[0067] Table 1 Enthalpy value variation diagram of Examples 1-5 and Comparative Example 1
[0068]
[0069] Microstructure measurement results
[0070] like Figure 3 As shown, the particles in Comparative Example 1 are mainly spherical, ellipsoidal or irregular in shape, with a relatively smooth surface and a small number of small pits. The complexes in Examples 1 to 5 will be partially gelatinized or fragmented, the starch particles disappear, and the starch forms rock-like starch blocks without a fixed form. Under a high-power microscope, obvious rod-shaped substances can be seen, which may be a combination of starch and lipids. When the moisture content of the system is 30%-50%, the particles of the starch-lipid complex have been destroyed, and oil is attached to the surface, wrapping the gelatinized starch. As the moisture content increases, the gelatinization phenomenon becomes more obvious, and the white-edged flaky structure on the starch surface is more obvious and dense. The reason is that safflower seed oil is liquid at room temperature, and because of its low viscosity, it is easier to form flaky starch. When the moisture content of the system is 30%, the relative crystallinity is the largest.
[0071] Oil absorption results
[0072] like Figure 4As shown, Comparative Example 1 exhibits a higher polarity due to the presence of surface hydroxyl groups, and water droplets spread rapidly on its surface with a contact angle of 43.7°. The contact angles of Examples 1 to 5 are all increased relative to the original starch. When the moisture content increases from 10% to 50%, its contact angle with safflower oil increases from 94.6° to 125.8°, showing a strong hydrophobic property. The results show that the addition of lipids can enhance the hydrophobicity of starch because the hydroxyl groups on the surface of the original starch are replaced by the long carbon chain of fatty acids, and its polarity decreases, and its affinity with water decreases. In addition, the contact angle of the composite increases with the increase of the composite index, and the magnitude of the enhancement may be related to the amount of composite formed. When the moisture content is 30%, the oil absorption effect is the strongest.
[0073] Solubility and Swelling Power Results
[0074] As shown in Figure 5, compared with Comparative Example 1, the solubility and swelling power of the composites with different moisture contents are significantly reduced, especially with the increase of temperature, the change trend is more obvious. With the increase of the moisture content of the system, when the moisture content is 10%-30%, the solubility and swelling power of the composite show a decreasing trend, and when it is 40%-50%, its solubility and swelling power begin to increase again. The reason is that with the increase of the moisture content of the system, the amylose is more likely to migrate, which promotes the formation of amylose-lipid complexes. However, when the moisture content of the system exceeds 40%, the starch forms a sticky texture due to gelatinization, the fluidity of amylose and lauric acid decreases, and the degree of composite decreases.
[0075] Freeze-thaw stability results
[0076] like Figure 6 As shown, with the increase of the number of freeze-thaw cycles, the dehydration rates of starch and the complexes all show an upward trend. Compared with the comparative example, the reason for the reduction in the dehydration rate of Examples 1 to 5 may be that lipids enter the internal structure of starch particles, causing the steric hindrance to increase, further inhibiting the rearrangement and association between starch molecules, and the two are closely combined through hydrophobic interactions, which can effectively delay the formation of the sponge state of starch gel structure during freeze-thaw, thereby inhibiting the precipitation of water molecules, indicating that the addition of lipids effectively reduces the dehydration rate of starch. The dehydration rate of starch-lipid shows a trend of first decreasing and then increasing with the increase of the water content of the system. Under low moisture content (10%-30%), with the increase of moisture content, it is beneficial to destroy the original starch structure and cause starch molecules to migrate, thereby promoting the interaction between linear starch molecular chains and between amylose and lipid molecules, forming more starch-lipid complexes, and excessive moisture (40%-50%) may cause starch to gelatinize in a high temperature environment, resulting in excessive destruction of starch molecules, which is not conducive to the formation of double helical crystalline structure and starch-lipid complexes.
[0077] In summary, hydrothermal treatment has a certain degree of degradation effect on starch chains, which can effectively increase the lipid content in the composite product. The solubility, swelling degree and freeze-thaw stability of the composite first decrease and then increase with water content, while the relative crystallinity, thermal stability and oil absorption first increase and then decrease. Among all the composites, when the moisture content is 30%, the solubility, swelling degree and freeze-thaw stability of the composite are the lowest, the relative crystallinity is the largest, and the thermal stability and oil absorption are the strongest.
[0078] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a starch-lipid complex, characterized in that: The following steps are involved: S1. Prepare a suspension of amylose or a mixture of amylopectin and amylose with distilled water to form a starch emulsion with a mass percentage of 30%, and stir it in a water bath at 80°C with a water bath magnetic stirrer for 1 h; S2. Take safflower oil and dissolve it in hot anhydrous ethanol, then add the solution to the starch paste in step S1, and then stir in a water bath for 1h; S3. The obtained sample was slowly cooled to room temperature, the prepared sample was taken out, centrifuged at 8000 r / min for 15 min, and then centrifuged and washed with a 50% by volume ethanol-water solution, and finally dried in an oven at 45°C overnight, crushed and sieved through a 100-200 mesh sieve.
2. The preparation method according to claim 1, characterized in that: When the starch is a mixture of amylopectin and amylose, the mixing ratio of amylopectin to amylose is 2:8-3:
7.
3. The preparation method according to claim 1, characterized in that: The safflower oil can also be replaced by one of linseed oil, palm oil, soybean oil, corn oil, cottonseed oil, coconut oil, tallow and lard.